Endoscopic ultrasonography‐guided pancreatic duct access: Techniques and literature review of pancreatography, transmural drainage and rendezvous techniques. Issue 3 (12th March 2013) - Itoi, Takao; Kasuya, Kazuhiko; Sofuni, Atsushi; Itokawa, Fumihide; Kurihara, Toshio; Yasuda, Ichiro; Nakai, Yousuke; Isayama, Hiroyuki; Moriyasu, Fuminori
<x xml:space="preserve">Abstract</x> Endoscopic ultrasonography‐guided (EUS)‐guided pancreatic interventions have gained increasing attention. Here we review EUS‐guided pancreatic duct (PD) access techniques and outcomes. EUS‐guided PD intervention is divided into two types, antegrade and rendezvous techniques, following EUS‐guided pancreatography. In the antegrade technique, pancreaticoenterostomy is carried out by stent placement between the PD and the stomach, duodenum, or jejunum. Transenteric antegrade PD stenting is conducted by stent placement, advancing anteriorly into the PD through the pancreatic tract. The rendezvous technique is carried out by using a guidewire through the papilla or anastomotic site for retrograde stent insertion. In terms of EUS‐guided PD stenting, 11 case reports totaling 75 patients (35 normal anatomy, 40 altered anatomy) have been published. The technical success rate was greater than 70%. Early adverse events, including severe hematoma and severe pancreatitis, occurred in seven (63.6%) of 11 reports. Regarding the rendezvous technique, 12 case reports totaling 52 patients (22 normal anatomy, 30 altered anatomy) have been published. The technical success rate ranged from 25% to 100%. It was 48% in one report that involved more than 20 cases. Once stents were placed, all patients became free of symptoms. Early mild adverse events occurred in four (36.4%) of 11 reports. In conclusion, although it can be risky because of possible serious or even fatal adverse events, including pancreatic juice leakage, perforation and severe acute pancreatitis, EUS‐PD access seems to be promising for treating symptomatic pancreatic diseases caused by PD stricture and pancreaticoenterostomy stricture.